Training in communication of oncology clinicians: a position paper based on the third consensus meeting among European experts in 2018. (9th November 2018) - Stiefel, F; Kiss, A; Salmon, P; Peters, S; Razavi, D; Cervantes, A; Margulies, A; Bourquin, C; ,
Abstract: Background: Since there is sound evidence that communication skills training (CST) programs modify communication behavior of oncology clinicians, they have been widely implemented over the last decades. However, more recently, certain aspects of this training have been criticized. Methods: Based on this background, a call to re-launch a discussion about the future of CST led to the third European consensus meeting on communication in cancer care, organized by the Swiss Cancer League. During this meeting, which brought together European experts in the field of clinical communication and training of communication in the oncology setting, oncology clinicians, representatives of the European Society of Medical Oncology and a member of the European Oncology Nursing Society, the recommendations of the second European consensus meeting were updated and expanded. Results: The expanded recommendations recall the guiding principles of communication in cancer care, underline the important role of clinician's self-awareness, and of relational and contextual factors in clinical communication, and provide direction for the further development of communication training. Conclusion: This third European consensus meeting defines key elements for the development of a next generation of communication training for oncology clinicians.